2019
DOI: 10.1155/2019/7690869
|View full text |Cite
|
Sign up to set email alerts
|

Network Growth Modeling to Capture Individual Lexical Learning

Abstract: Network models of language provide a systematic way of linking cognitive processes to the structure and connectivity of language. Using network growth models to capture learning, we focus on the study of the emergence of complexity in early language learners. Specifically, we capture the emergent structure of young toddler’s vocabularies through network growth models assuming underlying knowledge representations of semantic and phonological networks. In construction and analyses of these network growth models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Semantic networks have recently been used to explain individual differences in people's knowledge [29,30]. In these accounts, each person has a different semantic network, which is Funding: KVL was supported by the UW-Madison L&S Senior Honors Thesis Research Grant.…”
Section: Introductionmentioning
confidence: 99%
“…Semantic networks have recently been used to explain individual differences in people's knowledge [29,30]. In these accounts, each person has a different semantic network, which is Funding: KVL was supported by the UW-Madison L&S Senior Honors Thesis Research Grant.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the structure of the phonological lexicon has measurable influences on various language-related processes [ 7 , 8 , 9 ]. Research investigating the processes that facilitate the acquisition of the phonological form of a word indicate that phonological network growth may be driven by alternative network growth mechanisms other than the widely studied preferential attachment [ 10 , 11 , 12 ]. Central to the present study is a recent paper by Siew and Vitevitch [ 12 ], who conducted a longitudinal analysis of phonological networks of English and Dutch words and found that preferential attachment was a better predictor of acquisition than preferential acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative growth models have also been proposed; for instance, preferential acquisition (Hills, Maouene, Maouene, Sheya, & Smith, 2009 ) predicts that new words are more likely to be learnt if they are themselves well connected to other words in the learning environment, regardless of whether they are linked to a known word with many preexisting connections. It is, however, beyond the scope of the current article to offer an exhaustive comparison of these growth models; interested readers may consult these excellent articles: Beckage and Colunga ( 2019 ), Hills et al ( 2009 ), and Fourtassi, Bian, and Frank ( 2019 ).…”
mentioning
confidence: 99%